2000
DOI: 10.1103/physrevlett.85.3954
|View full text |Cite
|
Sign up to set email alerts
|

Charge Ordering and Polaron Formation in the Magnetoresistive OxideLa0.7Ca0.3MnO3

Abstract: Neutron scattering has been used to study the nature of the ferromagnetic transition in a single crystal of the perovskite La0. 7Ca0.3MnO3. Diffuse scattering from lattice polarons develops as the Curie temperature is approached from below, along with short range polaron correlations that are consistent with stripe formation. Both the scattering due to the polaron correlations and the anomalous quasielastic component in the magnetic fluctuation spectrum maximize very close to T(C), in a manner remarkably simil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
246
3
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(274 citation statements)
references
References 43 publications
23
246
3
2
Order By: Relevance
“…The similarity of the data suggests a common physical origin. The figure is taken from [55]. Similar results have been obtained in [59].…”
Section: Temperature Dependence and Incoherent Spin Dynamics Near T Csupporting
confidence: 74%
See 1 more Smart Citation
“…The similarity of the data suggests a common physical origin. The figure is taken from [55]. Similar results have been obtained in [59].…”
Section: Temperature Dependence and Incoherent Spin Dynamics Near T Csupporting
confidence: 74%
“…Figure 18 To further characterize the spin dynamics of FM manganites when T → T C several groups have studied the spin diffuse scattering near T C [19,23,25,26,51,52,55,56]. An anomalous and field-dependent central diffusive component which develops above T ∼ 0.8T C for La 0.7 Ca 0.3 MnO 3 [25] and T ∼ 0.9 T C for Nd 0.7 Sr 0.3 MnO 3 [23] and dominates the fluctuation spectrum as T → T C [25,23] has been observed for the low-T C samples, coinciding with the non-collapse behaviour of D(T ).…”
Section: Temperature Dependence and Incoherent Spin Dynamics Near T Cmentioning
confidence: 99%
“…19 of [6] for a more detailed discussion, preliminary information, and additional citations. For our purposes, here we will only describe the recent work of Adams et al [31] where neutron scattering results for La 1−x Ca x MnO 3 with x=0.30 were reported in a wide range of temperatures. Some results are in Fig.…”
Section: Phase Coexistence Above T C and Experimental Determination Omentioning
confidence: 99%
“…It was concluded that "The similarity of the data indicates a common origin". From Adams et al [31], where more details can be found.…”
Section: Phase Coexistence Above T C and Experimental Determination Omentioning
confidence: 99%
See 1 more Smart Citation